Spatial variations in Titan’s atmospheric temperature: ALMA and Cassini comparisons from 2012 to 2015 - Thelen, A; Nixon, C; Chanover, N; Molter, E; Cordiner, M; Achterberg, R; Serigano, J; Irwin, P; Teanby, N; Charnley, S (Elsevier, 2017)
Submillimeter emission lines of carbon monoxide (CO) in Titan's atmosphere provide excellent probes of atmospheric temperature due to the molecule's long chemical lifetime and stable, well constrained volume mixing ratio. Here we present the analysis of 4 datasets obtained with the Atacama Large Millimeter/Submillimeter Array (ALMA) in 2012, 2013, 2014, and 2015 that contain strong CO rotational transitions. Utilizing ALMA's high spatial resolution in the 2012, 2014, and 2015 observations, we extract spectra from 3 separate regions on Titan's disk using datasets with beam sizes ranging from 0.35 × 0.28'' to 0.39 × 0.34''. Temperature profiles retrieved by the NEMESIS radiative transfer code are compared to Cassini Composite Infrared Spectrometer (CIRS) and radio occultation science results from similar latitude regions. Disk-averaged temperature profiles stay relatively constant from year to year, while small seasonal variations in atmospheric temperature are present from 2012 to 2015 in the stratosphere and mesosphere (~100-500 km) of spatially resolved regions. We measure the stratopause (320 km) to increase in temperature by 5 K in northern latitudes from 2012 to 2015, while temperatures rise throughout the stratosphere at lower latitudes. We observe generally cooler temperatures in the lower stratosphere (~100 km) than those obtained through Cassini radio occultation measurements, with the notable exception of warming in the northern latitudes and the absence of previous instabilities; both of these results are indicators that Titan's lower atmosphere responds to seasonal effects, particularly at higher latitudes. While retrieved temperature profiles cover a range of latitudes in these observations, deviations from CIRS nadir maps and radio occultation measurements convolved with the ALMA beam-footprint are not found to be statistically significant, and discrepancies are often found to be less than 5 K throughout the atmosphere. ALMA's excellent sensitivity in the lower stratosphere (60-300 km) provides a highly complementary dataset to contemporary CIRS and radio science observations, including altitude regions where both of those measurement sets contain large uncertainties. The demonstrated utility of CO emission lines in the submillimeter as a tracer of Titan's atmospheric temperature lays the groundwork for future studies of other molecular species - particularly those that exhibit strong polar abundance enhancements or are pressure-broadened in the lower atmosphere, as temperature profiles are found to consistently vary with latitude in all three years by up to 15 K.